2 Jugendliche (Eskimo-und Ansiedler-mädchen) in europäischer Tracht in Hoffenthal 1920 - Bohlmann, Ernst, 1864-1945. (2001)
Photograph of two young women (an Inuk and a settler) wearing European style dresses at Hopedale mission station in 1920. Photograph of two young women (an Inuk and a settler) wearing European style dresses at Hopedale mission station in 1920.